External relations management of Malaysia principals - Alias, Bity Salwana; Zainudin, Zaida Nor (Scientific Research Publishing, 2018)
The concept of school management has been extensively studied, however only a few focused on the external relations management. Due to the statement in Malaysian Education Development Blueprint 2013-2025 that school managers are required to build a good collaboration with communities, this study aims to identify principals’ competency in managing external relations by measuring their knowledge and skills in those areas. This survey study involved 314 principals, 720 senior assistants, and 611 senior teachers all over Malaysia. The quantitative data were collected through questionnaire and were analyzed by SPSS to determine mean score and standard deviation. Finding shows that, in overall principals’ knowledge and skills are at a high level with the mean score 4.27 and 4.40 respectively. Principals’ knowledge on external sources that can benefit schools achieves the lowest (mean score 4.23), followed by knowledge on concept of cooperation between school and school/home/community (mean score 4.25), and knowledge on strategy to improve relationship between school and community (mean score 4.25). The lowest mean score for skills is influencing outsiders to contribute to the school fund (4.23), followed by handling criticism in a positive way (mean score 4.37), and showing appreciation to the communities’ involvement in school activities (mean score 4.37). This study concludes that principals’ competency can be at the best level if knowledge and skill in those aspects can be increased.